Atmospheric concentrations of persistent organic pollutants over the Pacific Ocean near southern Taiwan and the northern Philippines - Chao, How-Ran; Lin, Ding-Yan; Chen, Kuang-Yu; Gou, Yan-Yu; Chiou, Tsyr-Huei; Lee, Wen-Jhy; Chen, Shui-Jen; Wang, Lin-Chi (The Science of the total environment, 2014)
This study investigates the atmospheric occurrence of persistent organic pollutants (POPs) over the Pacific Ocean near southern Taiwan and the northern Philippines. We determined sixty-six compounds, including polychlorinated dibenzo-p-dioxins and dibenzofurans (PCDD/Fs), dioxin-like polychlorinated biphenyls (DLPCBs), polybrominated diphenyl ethers (PBDEs), as well as polychlorinated diphenyl ethers (PCDEs), polybrominated dibenzo-p-dioxins and dibenzofurans (PBDD/Fs), and polybrominated biphenyls (PBBs), in air samples simultaneously collected from the offshore oceanic atmosphere (n=6) and over a rural area (n=2). We calculated the atmospheric World Health Organization 2005 toxic equivalency levels (WHO2005-TEQ), for the total dioxin-like POPs, including PCDD/Fs, DLPCBs, and PBDD/Fs, being 0.00612pg WHO2005-TEQ/m3 and 0.0138pg WHO2005-TEQ/m3 over the ocean and land, respectively. We found unexpected lower averaged atmospheric PBDE concentrations in the rural area (15.9pg/m3) than over the ocean (31.1pg/m3) due to higher levels of the BDE209 congener, although the difference was not statistically significant. We have compared and reported our field results with previously published datasets over the global oceans, which suggest PCBs and PBDEs are the dominant chemical contaminants in the global oceanic atmosphere among these halogenated POPs (e.g. PCBs and Σdi-hepta PBDEs could be found in the range of 0.09–48.7 and 8.07–94.0pg/m3, respectively, including our dataset). However, there are still very few investigations on the global atmospheric levels of PBDD/Fs, PCDEs and PBBs and our data sums to these earlier studies. Finally, we point out that the halogenated POPs originated from Taiwan or the continental East Asia which could easily reach remote ocean sites via atmospheric transport. •The world's first data on PBDD/Fs, PCDEs, and PBBs in the oceanic atmosphere•Atmospheric POP TEQ levels over the target ocean were one order lower.•PCBs and PBDEs were the dominant POPs in the global oceanic atmosphere.•Atmospheric POPs over the target ocean were influenced by combustion sources.